2007
DOI: 10.1080/00016340601151683
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐related pelvic girdle pain in the Netherlands

Abstract: Normal obstetric procedures can be followed in women reporting pregnancy-related pelvic girdle pain. Prognosis is generally good, however, women reporting pelvic girdle pain 3 months after delivery need extra consideration. Attention needs to be given to psychosocial factors, in particular depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 38 publications
3
65
2
4
Order By: Relevance
“…41,43 Other research shows elevated depression among those with pregnancy-related LBP/PGP. 44,45 Activity limitations resulting from LBP/PGP during pregnancy and the postpartum period have been shown to interfere with weight loss and resumption of leisure-time physical activity levels needed for health maintenance. 46 Additionally, patients with both LBP and PGP have been found to be at greatest risk of persistent pain postpartum 47 and to experience greater disability.…”
Section: Occupational Lifting and Fetal-maternal Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…41,43 Other research shows elevated depression among those with pregnancy-related LBP/PGP. 44,45 Activity limitations resulting from LBP/PGP during pregnancy and the postpartum period have been shown to interfere with weight loss and resumption of leisure-time physical activity levels needed for health maintenance. 46 Additionally, patients with both LBP and PGP have been found to be at greatest risk of persistent pain postpartum 47 and to experience greater disability.…”
Section: Occupational Lifting and Fetal-maternal Health Outcomesmentioning
confidence: 99%
“…41,43 Other research shows elevated depression among those with pregnancy-related LBP/PGP. 44,45 MacDonald et alPage 3 Am J Obstet Gynecol. Author manuscript; available in PMC 2015 August 28.…”
mentioning
confidence: 99%
“…The covari- ates that confounded the estimate the most were: parity, overweight, smoking, and not working during day time, while the remaining factors had only a minor influence. In the literature, factors such as working in draft and cold, pushing and pulling, bending and twisting, stress/ depression, and family history of pelvic pain during pregnancy were also identified as risk factors of pelvic pain during pregnancy, but we had no information on these potential confounders and could not include them in the model (2,12,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the positive association between pain and PPD is added to data described in the literature 3,[12][13][14][15][16] . However, one has to stress that pain-related findings are frequently interpreted in terms of duration 3 , presence or absence [12][13][14][15] , without quantifying intensity or considering whether this factor influences depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, one has to stress that pain-related findings are frequently interpreted in terms of duration 3 , presence or absence [12][13][14][15] , without quantifying intensity or considering whether this factor influences depressive symptoms. Our results have shown that, in addition to the relation between these variables, pain intensity referred in the postpartum period may be a predictive signal of depression.…”
Section: Discussionmentioning
confidence: 99%